Trends in composite materials and their design - Taha, Mohamed A.; El-Sabbagh, Ahmed M.; Taha, Iman M. (Key engineering materials, 2010)
Composite materials are increasingly finding use in diverse applications requiring a wide range of property and performance requirements. Low density, high specific strength and stiffness are the main features that make composite materials most suitable for structural applications. The field covers the concurrent manipulation of the material's composition and of the internal architecture of the composite in order to obtain the desired properties. The ability to tailor composite materials precisely is of great importance in structural applications. A systematic approach to the optimum tailoring.